Wireless Sensor Networks- A Review on Topologies and Node Architecture - Sharma, Shamneesh; Kumar, Dinesh; Kishore, Keshav (International Journal of Computer Sciences and Engineering, 2013)
This review paper basically divided in two parts out of which first part focuses on the existing topologies that are used in the wireless sensor networks and second part emphasis on the architecture of the node. As we all know that wireless sensor network technology is the application oriented technology so topology and architecture of the network will always vary from application to application i.e. dynamic in nature. The development and deployment of the nodes always differ from traditional technologies; no doubt initially the traditional technology has been used but the excessive use of traditional technology changed the scenario. Now these topologies are used with hybrid techniques i.e. topologies with additional features & advantages and same the case with node architecture. As many of WSN applications need the networking alternatives to improve the cost reduction, efficiency and security aspects so in this review report we are discussing all the topologies used and the hybridized changes that had been done in past and can be done in future on the architecture of the WSN node.